2020
DOI: 10.13189/ujer.2020.080126
|View full text |Cite
|
Sign up to set email alerts
|

Improved Learning Design for Pre-Service Teacher in a Character Education Course

Abstract: This study aimed to develop pre-service teachers' engagement in a character education course through new learning design of a RECE (Reflect, Engage, Collaborate and Elaborate) teaching model, in the Pancasila and Citizenship Education department of a university. RECE involve self-reflections and collaborative learning. The RECE active learning and teaching model was implemented to engage pre-service teachers in challenging classroom environments. The study was conducted with 65 pre-service teachers in their fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Related to teaching practice activity, every planned printed teaching and learning activity containing related materials is sought to consult the school subject teacher based on the subject's curriculum. Practically, every planned printed teaching and learning activity should be consulted and agreed upon by both school subject teachers and lecturers (Afalla & Fabelico, 2020;Sarkadi et al, 2020). The number of printed teaching and learning activities done by the pre-service teacher is based on the varied materials and meetings, at least done in ten meetings.…”
Section: Introductionmentioning
confidence: 99%
“…Related to teaching practice activity, every planned printed teaching and learning activity containing related materials is sought to consult the school subject teacher based on the subject's curriculum. Practically, every planned printed teaching and learning activity should be consulted and agreed upon by both school subject teachers and lecturers (Afalla & Fabelico, 2020;Sarkadi et al, 2020). The number of printed teaching and learning activities done by the pre-service teacher is based on the varied materials and meetings, at least done in ten meetings.…”
Section: Introductionmentioning
confidence: 99%
“…(2) has a commitment and awareness of social and human values. (3) have the ability to communicate, cooperate, and compete in a pluralistic society at the local, national and global levels (Sarkadi, Casmana, & Rahmawati, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The learning quality components include: teacher quality, student motivation and attitudes, learning infrastructure and learning climate, while the output component includes academic skills, social skills and personal skills. This model was developed as a combination of the CIPP evaluation model (context, input, process, product) of Stufflebeam and Kirkpatrick (Sarkadi, Casmana, & Rahmawati, 2020). The results of the development of the recommended EKOP model can be used as an alternative for school leaders to evaluate social studies learning programs in junior high schools.…”
Section: Introductionmentioning
confidence: 99%
“…The results of other research conducted by Pradewi & Rukiyati (2019), showed that: (1) zoning facilitates access to education services, (2) zoning equalizes the quality of schools, (3) zoning decreases the quality of schools, (4) zoning does not fit at the level SMA (senior high school), (5) zoning system restricts students from choosing schools, (6) zoning policies must be accompanied by equal distribution of educational facilities and infrastructure, and (7) zoning destroys diversity (Pradewi, 2019;Sarkadi, Casmana, & Rahmawati, 2020). Then Marini & Utoyo (2019), the results of his research show that the zoning system policy has helped reduce the gap between the two schools studied, because students who are accepted come from different circles, different from before which was only filled with capable students in terms of its achievements and economy (Marini & Utoyo , 2019).…”
Section: Introductionmentioning
confidence: 99%